(untitled) (International Journal of Engineering and Computer Science, 2017)
Optical communication is a form of telecommunication that uses light as carrier and optical fiber as a transmission medium. Optical communication meant for long haul communication has been intended for an eight channel Wavelength Division Multiplexing (WDM) system. Dispersion is the major effect present in the optical fiber which causes a broadening of pulses and leads to Inter Symbol Interference (ISI). The dispersion effect is compensated by using Optical Phase Conjugation (OPC) technique which utilizes Four Wave Mixing (FWM) as the non-linear degrading effect. It has been found that the apposite modulation format for the transmitter part of the optical system is the Modified Duobinary Return-to-Zero (MDRZ) when compared it with Return-to-Zero (RZ), Non-Return-to-Zero (NRZ), Carrier-Suppressed Return-to-Zero (CSRZ) and Duobinary modulation formats. Dispersion Compensation Fiber (DCF) is used in this case which compensates the dispersion present in the fiber. The feat of the intended system is scrutinized in terms of eye opening, spectrum, bit error rate, Q-value etc.